Perspectives of Refugees from Ukraine on Cultural Identity and Health Care Experiences During U.S. Resettlement - Marianne R. Choufani; Kim L. Larson; Marina Y. Prannik (Nursing Reports)
Background: More than three years have elapsed since the onset of the full-scale invasion of Ukraine by the Russian Federation, displacing millions of Ukrainians. While preserving cultural identity in the host country is important for gaining resilience among refugees, we found no studies about how cultural identity influences health care experiences during resettlement. Objective: This study explores how cultural identity shapes health care experiences among Ukrainian refugees during resettlement in the United States. Methods: We conducted an interpretive description study using focus groups to elicit the perspectives of Ukrainian refugees who resettled in North Carolina after 24 February 2022. Twelve Ukrainian women participated in one of four focus groups. Thematic content analysis was employed for case comparison, and themes were inductively derived. Results: Two themes were identified: troubled health care partnerships and imprecise notions of preventive practices. Troubled partnerships represented a lack of trust between refugees and U.S. clinicians and the health care system. Imprecise notions of preventive practices represented mistaken beliefs about prevention. Conclusions: This study adds to the science on refugee health in two ways. First, newly arrived refugees often maintain strong ties to their homeland, which shapes their health care decisions and reinforces their cultural identity. Second, despite being well educated, some refugees held misconceptions about preventive health care, highlighting the need for clinicians to provide clear guidance on primary and secondary prevention practices. Findings may help guide clinicians in delivering culturally sensitive care to refugee populations.